Pengaruh Serat Ijuk Pada Campuran AC–WC Dengan Menggunakan Batu Gunung Bulu Tajongi - Yosilpa Kiding Rupa; Alpius; Elizabeth (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Laston as a surface layer or as a wear / AC-WC (Asphaltic Concrete-Wearing Course) layer is a pavement layer that is directly related to vehicle tires, a layer that must be waterproof, and resistant to weather. This study was conducted to determine the characteristics of the AC-WC mixture using Mount Bulu Tajongi Stone in East Luwu Regency and Ijuk Fiber as the added material. This research method used aggregation characteristics, filler characteristics, and asphalt characteristics, is a secondary data. Continued with the composition of the AC-WC mixture with fiber. The results of the analysis with the addition of ijuk fiber obtained a minimum stability value of 1000 kg at an ijuk fiber content of 4.77%, and a maximum stability of 1581.13 kg was at a fiber content of 2.20%, the minimum value of VIM was at a fiber content of 12.04%, the minimum value of Flow was at a fiber content of 5.07%, the minimum VMA value at a fiber content of 5.10%, and the VFB value had met the minimum limit of 65% of the fiber content of 0% - 4%. With Conventional Marshall testing, the results of the test object test analysis with the lowest stability value of 5% asphalt content meet the 2018 Bina Marga Specification Standards. So it can be concluded that ijuk fiber is suitable for use as an added ingredient.